Transformation of social values in modern conditions (Journal of Philosophy Culture and Political Science, 2018)
The interrelation of personality and social values has recently attracted the increasing attention of researchers in the context of considering the processes of globalization and market relations. It is traditionally considered that in a conceptual sense, value expresses the mode of existence of an individual. Moreover, different values have different meanings for it, and a hierarchy of values is associated with this. Like the values themselves, their hierarchical structure is of a concrete historical and personal nature.